In Vitro Characterization of Poly(Lactic Acid)/ Poly(Hydroxybutyrate)/ Thermoplastic Starch Blends for Tissue Engineering Application - Culenova, Martina; Birova, Ivana; Alexy, Pavol; Galfyova, Paulina; Nicodemou, Andreas; Moncmanova, Barbora; Plavec, Roderik; Tomanova, Katarina; Mencik, Premysl; Ziaran, Stanislav; Danisovic, Lubos (Cell transplantation, 2021)
Complex in vitro characterization of a blended material based on Poly(Lactic Acid), Poly(Hydroxybutyrate), and Thermoplastic Starch (PLA/PHB/TPS) was performed in order to evaluate its potential for application in the field of tissue engineering. We focused on the biological behavior of the material as well as its mechanical and morphological properties. We also focused on the potential of the blend to be processed by the 3D printer which would allow the fabrication of the custom-made scaffold. Several blends recipes were prepared and characterized. This material was then studied in the context of scaffold fabrication. Scaffold porosity, wettability, and cell-scaffold interaction were evaluated as well. MTT test and the direct contact cytotoxicity test were applied in order to evaluate the toxic potential of the blended material. Biocompatibility studies were performed on the human chondrocytes. According to our results, we assume that material had no toxic effect on the cell culture and therefore could be considered as biocompatible. Moreover, PLA/PHB/TPS blend is applicable for 3D printing. Printed scaffolds had highly porous morphology and were able to absorb water as well. In addition, cells could adhere and proliferate on the scaffold surface. We conclude that this blend has potential for scaffold engineering.
Keywords: tissue engineering; Tissue Engineering; 3D tisk; porosity; viscosimetry; Printing, Three-Dimensional; Humans; polyestery; Hydroxybutyrates; hydroxybutyráty; lidé; tkáňové inženýrství; Polyesters; 3D printing; PLA/PHB/TPS blend; biocompatibility